French Literature: From Realism to Magical Realism - Ali Shahab; Faruk Faruk; Arif Rokhman (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2020)
The purpose of the article is to explore the evolution of French literature between the late 19th century and early 21st century. Although French literature has long been dominated by rationalistic ways of thinking, based on the thoughts of René Descartes and John Locke, authors have used different means to express their perceptions of society. The novel Madame Bovary (1856), including its depiction of conjugal relationships, can be considered to have pioneered realism in French literature. During the Second World War, existentialism and absurdism appeared as new ways of examining not only the relationship among humans, but also between humans and God. In the late 20th century, magical realism emerged as a new literary stream that explicitly recognized the irrationality of human thinking. This article finds that the rationality of realism was necessary for magical realism to be accepted; in this rationality, although works of magical realism were irrational, they had to be recognized as fine examples of French literature that embodied such revolutionary ideas as liberté (liberty), égalité (equality), and fraternité (fraternity). To study this phenomenon, we examine the history of french literature by applying archeological method in order to understand the world views of the authors and how they change over time.